2018
DOI: 10.1007/s00415-018-8874-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlation and segregation of multimodal MRI abnormalities in multiple system atrophy

Abstract: Multimodal structural MRI abnormalities in MSA appear to be segregated into BG and stem-CB-related factors that can be associated with the clinical phenotype and motor severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…After hypometabolism maps, they reached the highest accuracy among diseases, and it did not improve after hypermetabolism maps. In both groups, however, the use of hypermetabolism maps increases confidence, maybe because of the confirmation that there is a metabolic sparing of cortical regions [ 24 , 25 ]. In the cases of PSP disease, one of the lowest accuracy levels after qualitative assessment happens in both experts and not experts, improving after hypometabolism maps in both groups and after hypermetabolism maps only in not experts.…”
Section: Discussionmentioning
confidence: 99%
“…After hypometabolism maps, they reached the highest accuracy among diseases, and it did not improve after hypermetabolism maps. In both groups, however, the use of hypermetabolism maps increases confidence, maybe because of the confirmation that there is a metabolic sparing of cortical regions [ 24 , 25 ]. In the cases of PSP disease, one of the lowest accuracy levels after qualitative assessment happens in both experts and not experts, improving after hypometabolism maps in both groups and after hypermetabolism maps only in not experts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of correlations between R2 * values and the degree of Unified Parkinson's Disease Rating Scale scores in PSP, the burden of iron-related PSP pathologies in the lenticular nucleus was associated with the severity of rigidity, and nigro-striato-pallidal and dentate iron content were associated with the severity of tremors (62). Other studies have failed to show a correlation of iron-sensitive MRI markers with clinical severity scale scores in MSA and PSP (34, 43, 49, 64), but have instead reported that diffusion tensor metrics, such as MD values, are closely correlated with clinical severity (63, 64). Iron-sensitive MRI markers may have less sensitivity to reflect clinical status than diffusion tensor metrics.…”
Section: Clinical Implications Of Brain Iron Deposition In Apsmentioning
confidence: 99%
“…Structural MRI abnormalities in MSA are segregated into basal ganglia and brainstem-cerebellar factors (64). Alterations in the R2 * of the basal ganglia region are not significantly correlated with the MRI variables associated with brainstem-cerebellar degeneration.…”
Section: Clinical Implications Of Brain Iron Deposition In Apsmentioning
confidence: 99%
“…Brain modifications related to neurodegeneration due to aging as well as psychiatric or neurodegenerative diseases can be characterized using multimodal MRI protocols with sequences sensitive to different tissue characteristics (Barbagallo et al, 2016; Cherubini et al, 2016; Eustache et al, 2016; Lee et al, 2018; Nemmi et al, 2015; Péran et al, 2010, Péran et al, 2018; Spoletini et al, 2011). Previous multimodal MRI studies have mainly used structural markers: grey and white matter volume (calculated using T1-weighted imaging), microstructural integrity of the white and grey matter by using diffusion weighted imaging (DWI) related indexes (e.g.…”
Section: Introductionmentioning
confidence: 99%